Corporate Diversification and CEO Compensation: Evidence from the Moderating Effect of Firm Size - Hwei C Wang; chih c fang; Yung-I Lou; Randall Zhaohui Xu; Ya Ying Chou Yeh (STIE Malangkucecwara, 2022)
This study explores whether firm size moderates the relationship between corporate diversification and CEO compensation. A sample of 2,448 CEO compensations across 1,622 firms from 1997 to 2002 was used to test several hypotheses. Corporate diversification was divided into two categories (international diversification and industry diversification) and firm size was defined using total assets. This study uses firm size as the moderator to test whether firm size influences the relationship between international diversification and CEO compensation. This study found new evidence that firm size moderate the relationship between both international diversification and industrial diversification and CEO total compensation. The result shows that firm size significantly and positively influences the relationship between International diversification and CEO compensation. Furthermore, the finding also shows that firm size significantly and negatively influences the relationship between industrial diversification and CEO compensation.